A facile and efficient synthesis of hexahydro-1H-pyrido[2, 3-b]indol-2-one scaffolds via a sequential Michael addition/amidation/reductive cyclization process. Issue 50 (16th December 2015) - Liu, Xiong-Li; Zhang, Wen-Hui; Yao, Zhen; Liu, Xiong-Wei; Peng, Li-Jun; Zhao, Zhi; Lu, Yi; Zhou, Ying; Yuan, Wei-Cheng
Abstract: A new methodology was developed for the synthesis of hexahydro-1 H -pyrido[2, 3- b ]indol-2-one scaffolds via a sequential Michael addition/amidation/reductive cyclization process. A wide variety of products bearing a hexahydro-1 H -pyrido[2, 3- b ]indol-2-one core with varying degrees of substitution around it, which is a key structural skeleton found in a large number of biologically active natural products and pharmaceutical compounds, were obtained smoothly with high efficiency (up to overall yield of 67%). Furthermore, their biological activities have been preliminarily demonstrated by in vitro evaluation against human prostate cancer cells PC-3, human lung cancer cells A549 and human leukemia cells K562 by the MTT-based assays, using the commercially available standard drug Cisplatin as a positive control. These results suggested there is a trend that lipophilic groups improve the potency, and also suggested a carbonyl moiety located in the hexahydro-1 H -pyrido[2, 3- b ]indol-2-one scaffolds is beneficial for the activity. The results also demonstrated that most of the compounds showed considerable cytotoxicities to these three cell lines K562, A549 and PC-3, and that hexahydro-1 H -pyrido[2, 3- b ]indol-2-one scaffolds may be potential leads for further antitumor activity screenings. Graphical abstract: